2019
DOI: 10.1038/s41598-019-48548-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific and glucocorticoid-responsive serum biomarkers for Duchenne Muscular Dystrophy

Abstract: Extensive biomarker discoveries for DMD have occurred in the past 7 years, and a vast array of these biomarkers were confirmed in independent cohorts and across different laboratories. In these previous studies, glucocorticoids and age were two major confounding variables. In this new study, using SomaScan technology and focusing on a subset of young DMD patients who were not yet treated with glucocorticoids, we identified 108 elevated and 70 decreased proteins in DMD relative to age matched healthy controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 49 publications
9
76
0
Order By: Relevance
“…In the first part of this pilot study, serum protein data for 12 healthy pediatric controls were from another independent study [22] and were employed as a bench mark for the initial exploratory comparison with the JDM data. In contrast, for the ELISA validation, healthy age, gender, matched controls were recruited (n = 17), and informed written consent was obtained from the parents/legally authorized representatives for those subjects aged up to 18 years, informed written assent obtained from those aged 12-17.9 years.…”
Section: Pediatric Controlsmentioning
confidence: 99%
“…In the first part of this pilot study, serum protein data for 12 healthy pediatric controls were from another independent study [22] and were employed as a bench mark for the initial exploratory comparison with the JDM data. In contrast, for the ELISA validation, healthy age, gender, matched controls were recruited (n = 17), and informed written consent was obtained from the parents/legally authorized representatives for those subjects aged up to 18 years, informed written assent obtained from those aged 12-17.9 years.…”
Section: Pediatric Controlsmentioning
confidence: 99%
“…We and others have shown that circulating levels of ApN are greatly decreased in mdx mice (mouse model of DMD) [56,100], an observation confirmed in human patients [101]. Moreover, myotubes from DMD patients were unable to produce ApN for local protection [57], unlike non-dystrophic myotubes challenged by inflammation [36].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 66%
“…In particular, the guidelines for enhanced validation of antibodies designed by the International Working Group for Antibody Validation (IWGAV), an ad-hoc formed group of leading researchers, promotes rigorous validation of such reagents and has been adopted by researchers and leading antibody producers [89][90][91]. Beside antibodies development of short single-stranded oligonucleotides as affinity reagents and the SomaLogic technology enabled researchers to analyze more than 1,000 targets in cross-sectional studies in the context of DMD [92][93][94][95][96]. The assay relies on the capture of the target in its native conformation to immobilized protein-specific Slow Off-rate Modified DNA aptamers (SOMAmers).…”
Section: Proteomic Technologies and Biomarker Discovery And Validationmentioning
confidence: 99%
“…Beside inflammation, DMD disease progression is also associated with increasing fibrosis. Proteins like IL-6, Interleukin 10 and INF-γ and Interleukin 13 are suitable for monitoring fibrosis at different disease stages [92,94,118,121]. Biomarkers associated with muscle function, inflammation, and fibrosis may recapitulate disease progression but additional biomarkers are required for the development of therapies.…”
Section: Biomarkers For Dmdmentioning
confidence: 99%
See 1 more Smart Citation